Optimization and Evaluation of Azithromycin-Loaded Organogels: In- Vitro Characterization and Rheological Behavior Studies - Behera, Pradipta Ranjan; Gajbhiye, Asmita; Patil, Shailendra (Journal of Neonatal Surgery, 2025)
This research aims to formulate azithromycin organogels for the localized treatment of skin infections, such as acne vulgaris and wound infections. By delivering azithromycin topically, the study seeks to minimize systemic side effects like diarrhoea, nausea, and abdominal pain. This approach offers a non-invasive administration method, avoids first-pass metabolism, improves patient compliance, suits nauseated individuals, reduces dosage through direct application to affected areas, and enhances overall acceptance. Additionally, the gel serves as a scaffold biomaterial to support wound healing. Findings indicate that an IPM-Lecithin (300 mM) oleogel with Carbopol 940 as an organogelator is a promising delivery system. The organogels were optimized by varying concentrations of Carbopol 940, Isopropyl Alcohol, and Propylene Glycol, while maintaining a fixed Triethanolamine weight ratio. A pilot study identified the lecithin-based azithromycin oleogel as the most effective formulation, prompting further investigation. Results highlight its ability to accelerate healing of Propionibacterium acnes-related infected acne, alongside demonstrating stability, safety, and cost-effectiveness as key antibacterial attributes...